Comparison of laryngeal mask airway insertion methods, including the external larynx lift with pre-inflated cuff, on postoperative pharyngolaryngeal complications: A randomised clinical trial. Issue 7 (July 2017) - Hu, Ling-Qun; Leavitt, Olga S.; Malwitz, Christine; Kim, Haisook; Doty, Robert A.; McCarthy, Robert J.
Abstract : BACKGROUND: Postoperative pharyngolaryngeal complications are commonly reported following laryngeal mask airway (LMA) insertion. After induction of anaesthesia, the airway structures fall backwards under the influence of gravity, and this may contribute to difficulty in placement of a LMA. External airway alignment by lifting the larynx during insertion of an airway may avoid collision of the airway with laryngeal structures. OBJECTIVE(S): To compare pharyngolaryngeal complications after either conventional airway insertion with or without cuff semi-inflation and a method, including an external larynx lift. DESIGN: Randomised controlled, double-blind, clinical trial. SETTING: Ambulatory surgical operating rooms of a university hospital. PATIENTS: American Society of Anaesthesiologists class 1 to 3 patients undergoing ambulatory surgery scheduled to receive general anaesthesia for which a LMA was not contraindicated. INTERVENTIONS: Patients were randomised into three groups for LMA placement: G1, deflated airway; G2, pre-inflated cuff; G3, pre-inflated cuff with external lifting of the larynx. Assessment of pharyngolaryngeal complications (blinded assessor) was made at the time of LMA removal and again at 1, 2 and 24 h. MAIN OUTCOME MEASURES: A pharyngolaryngeal complication, defined as a composite of one or more of sore throat, dysphonia or dysphagia at any time point, or blood on the airway at removal. RESULTS: Of the 450 consecutive patients, 441 were studied. There were no differences in insertion times or number of insertion attempts among the groups. There was no difference in pharyngolaryngeal complications among the groups: G1, 57%; G2, 55%; G3, 52%, ( P  = 0.77). Blood on the airway was observed less frequently in G3 (9%) compared with G1 and G2 combined (17%): difference −8% (95% confidence interval of the difference −0.8 to −16%, P  = 0.01). CONCLUSION: The external larynx lift technique was associated with a lower incidence of blood on the airway at removal, suggesting that the method may decrease trauma to the tissues of the upper airway during insertion. TRIAL REGISTRATION: Clinicaltrials.gov identifier: NCT01749033.